2012
DOI: 10.1111/j.1365-2958.2012.08002.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of csgD by the small regulatory RNA RprA links stationary phase, biofilm formation and cell envelope stress in Escherichia coli

Abstract: RprA is a small regulatory RNA known to weakly affect the translation of σS (RpoS) in Escherichia coli. Here we demonstrate that csgD, which encodes a stationary phase-induced biofilm regulator, as well as ydaM, which encodes a diguanylate cyclase involved in activating csgD transcription, are novel negatively controlled RprA targets. As shown by extensive mutational analysis, direct binding of RprA to the 5′-untranslated and translational initiation regions of csgD mRNA inhibits translation and reduces csgD m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
143
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(145 citation statements)
references
References 59 publications
(89 reference statements)
1
143
1
Order By: Relevance
“…1C). We did not observe the previously reported RprA-mediated repression of csgD (35,36), perhaps because the csgD promoter was silent under the experimental conditions used here (37). This notwithstanding, our pulse expression data suggested that the two forms of RprA recognize several targets by different seed regions and predicted processed RprA to be a regulator in its own right.…”
Section: Resultscontrasting
confidence: 46%
See 1 more Smart Citation
“…1C). We did not observe the previously reported RprA-mediated repression of csgD (35,36), perhaps because the csgD promoter was silent under the experimental conditions used here (37). This notwithstanding, our pulse expression data suggested that the two forms of RprA recognize several targets by different seed regions and predicted processed RprA to be a regulator in its own right.…”
Section: Resultscontrasting
confidence: 46%
“…Other environmental factors activating σ S independent of RprA will not affect RicI expression and plasmid transfer. In E. coli, a similar diversification of the σ S regulon is present with csgD and ydaM: although σ S activates these two genes for curli fiber and cellulose production, RprA represses their mRNAs (35,68), suggesting that RprA promotes certain stress-related functions of the σ S regulon but inhibits the functions of CsgD and YdaM.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, RprA is involved in up-regulation of its mRNA target, rpoS, through pairing to the 5 ′ UTR of rpoS, relieving the inhibitory secondary structure around the RBS and thereby supporting its translation (Updegrove et al 2008). Interestingly, RprA has recently been identified as being involved in down-regulation of two other mRNAs, namely, csgD and ydaM (Mika et al 2012). Hence while RprA protection from RNase E appears to be transmitted to its mRNA target, rpoS, to support up-regulation, the full picture is evidently complex with no immediate correlation between RNase E protection and sRNA function.…”
Section: Discussionmentioning
confidence: 99%
“…OmrA, OmrB, RprA, GcvB, and McaS all bind upstream of the ribosome-binding site and their mode of action likely involves inhibition of translational initiation and/or mRNA destabilization (Holmqvist et al, 2010;Jørgensen et al, 2012;Mika et al, 2012;Thomason et al, 2012).…”
Section: Introductionmentioning
confidence: 99%